2018
DOI: 10.1109/tns.2018.2823540
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Suitability of NEON SIMD Microprocessor Extensions Under Proton Irradiation

Abstract: This work analyzes the suitability of SIMD (Single Instruction Multiple Data) extensions of current microprocessors under radiation environments. SIMD extensions are intended for software acceleration, focusing mostly in applications that require high computational effort, which are common in many fields such as computer vision. SIMD extensions use a dedicated coprocessor that makes possible packing several instructions in one single extended instruction. Applications that require high performance could benefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…The most recent applications of the CNA 60 Co irradiator have been mainly focussed in to analyze dose effects in different electronic systems: unclonable functions implemented in FPGAs [37] and SIMD microprocessors [38,39].…”
Section: Co-60 Irradiatormentioning
confidence: 99%
“…The most recent applications of the CNA 60 Co irradiator have been mainly focussed in to analyze dose effects in different electronic systems: unclonable functions implemented in FPGAs [37] and SIMD microprocessors [38,39].…”
Section: Co-60 Irradiatormentioning
confidence: 99%
“…In this particular case, the DUT was placed at 53.5 cm from the exit nozzle, so that the final energy at the surface was 15.2 MeV, with an estimated spread in the order of 300 KeV. The device package was not removed, as the energy range of incident protons in the silicon active area (8 to 10 MeV) was sufficient to produce events, which has previously been validated by the CNA group in similar campaigns conducted with these types of boards [7]. The final energy of the incident beam on the surface and in the active area was obtained with energy-loss data calculated with the SRIM2013 code [39].…”
Section: B Facilities -Lansce and Cnamentioning
confidence: 99%
“…In addition, the resulting custom hardware is targeted at a specific device and therefore a very expensive solution. In contrast, Software-Implemented Hardware Fault Tolerance (SIHFT) [7], [8] is a software programming approach to deal with faults affecting the hardware. These approaches are less expensive and have shorter development timelines than the hardware approaches.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the DUT was placed at 53.5 cm from the exit nozzle with a mylar foil window of 125µm, so that the final energy at the surface was 15.2 MeV, with an estimated spread of ∼300 KeV. Previous tests at the CNA have shown that the energy range of incident protons in the silicon active area, 10 to 8 MeV, is sufficient to produce events without thinning them [24]. The final energy of the incident beam at the surface and in the active area was obtained by using the energy loss data calculated with the SRIM2013 code [25].…”
Section: B Mooga Parametersmentioning
confidence: 99%